إسهامات الشيخ أحمد سَنُوسي ومنهجُه في معالجة القضايا المعاصِرة من خلال تفاسيره للقرآن الكريم : دراسة تحليلية - يوسف، أحمد محمد
The interest of researchers in the study of the books of Tafsir in regional or local languages - especially the Sundanese - is still little and rare, although such interpretative works in fact play an important role in inculcating Islamic awareness in the community of these languages, as its language may be more effective in Islamic cultural influence. This thesis aims at highlighting the personality of the interpreter Shaykh Ahmad Sanusi (1888-1950) from Sukabumi region of Western Java, and to expose his efforts in the Da'wah, educational and political movement. And to introduce his three books of Tafsir, namely, Tafsir “Malja' at Thalibin fii Tafsir Kalami Rabbil 'Alamiin”, Tafsir “Tamshiyat al Muslimin fii Tafsir Kalami Rabbil 'Alamiin” and Tafsir “Raudhat al 'Irfan fii Ma'rifatil Qur'an”. This thesis also attemps to study the contributions of Shaykh Ahmad Sanusi and his methodology in handling the contemporary issues in Indonesia through his interaction with the Qur'anic verses. The study followed an analytical and inductive method in which it relies on the methods of library research as well as individual analytical interpretations. This study has produced many results, the most important of which is the assertion that Shaykh Ahmad Sanusi is one of the most prominent figures and scholars in West Java, based on his role and commendable efforts in the field of Tafsir, authorization, education and politics. The study also demonstrates that Shaykh Ahmad Sanusi has remarkable efforts in handling the contemporary issues in Indonesia through his deductions of the Qur'anic verses which include various aspects of religious, social, political and scientific issues, which show the Shaykh's interest in unifying Muslims and the necessity of performing Da'wah to Allah, and his struggling against western colonialism and intellectual stagnation among Muslims.